Growth drivers in emerging capitalist economies: building blocks for a post-Keynesian analysis and an empirical exploration of the years before and after the Global Financial Crisis - Benjamin Jungmann (Review of Evolutionary Political Economy, 2023)
This paper contributes to the growth models debate by expanding the concept of growth drivers to emerging capitalist economies (ECEs). Conceptually, the paper synthesizes growth drivers with a growth model operationalization based on GDP growth contributions and financial sector balances. Drawing on post-Keynesian and structuralist economics, as well as, empirical studies, seven growth drivers for ECEs are reviewed: income distribution, price and non-price competitiveness, commodity prices, private debt, foreign direct investment (FDI) and fiscal policy. Descriptive data for these drivers are presented for 19 regionally grouped ECEs between 2000 and 2019. On average, Asian ECEs exhibit higher growth rates, stable real exchange rates, high and increasing non-price competitiveness and high private debt levels. Latin American countries show comparatively lower growth rates, high but decreasing income inequality, unstable exchange rates and relatively expansionary fiscal policy after the Global Financial Crisis (GFC). Central and Eastern European countries generally display medium to high growth rates, lower income inequality, high non-price competitiveness, a substantial FDI stock and, after the GFC, real depreciations and contractionary fiscal policy. The assessment of cross-country growth drivers via bivariate coefficients reveals limited robust results, except for non-price competitiveness, which emerges as a significant driver. Additionally, we find indications that private debt and expansionary fiscal policy became more important for growth in ECEs after the GFC. This is in line with the emergence of domestic demand- and private debt-led growth models in ECEs following the GFC in the course of private deleveraging and austerity policies in developed capitalist economies.
Keywords: E11; E12; E65; F62; F65; 320; Growth model; Growth driver; Financialisation; Emerging economies; Post-Keynesian economics; Comparative political economy